O papel da comunidade educativa cedac na política de formação continuada dos profissionais de educação no município de venda nova do imigrante - Carvalho, Leandro Daniel Santos [UNIFESP] (2015)
The object of this case study is a continuous formation project of education professionals, developed in the city of Venda Nova do Imigrante - ES. As a result of a partnership between Comunidade Educativa CEDAC, Instituto Jutta Batista and the city of Venda Nova do Imigrante, o Projeto Escola began in 2013 and has discontinued in 2014. Adopting the Robert Yin case study perspective, the study has as main objective understand how Comunidade Educativa CEDAC has contributed to the development of the continuous formation policy in Venda Nova do Imigrante, through Projeto Escola. The research used as main methods in-depth interviews and focus group with teachers, directors and pedagogical coordinators of city childhood education, participants of the project. Has been developed an analytical reference that focused two main analytics dimensions: Implementation and relation of the project to context and Changes and transformations related to the project. The data analyses, accomplished by triangulation with the different actors, highlights that there was a significant redefinition of concepts e practices of childhood education in Venda Nova do Imigrante, that was supported and sustained by a dynamic e decentralized continuous formation policy in the schools. The formation flows, the structural documents and the focus and commitment with the childhood learning has been acting as important aspect to the continued improvement in this segment in the city.